2021
DOI: 10.3390/ijerph18116026
|View full text |Cite
|
Sign up to set email alerts
|

The Deviation of the Behaviors of Rice Farmers from Their Stated Willingness to Apply Biopesticides—A Study Carried Out in Jilin Province of China

Abstract: The substitution of chemical pesticides by biopesticides is crucial to ensure the quality of agricultural products and to foster environmental sustainability. This study takes the willingness and the behaviors of rice farmers on the application of biopesticides as the research object. The survey questionnaire was designed based on the theory of rational small-scale farmers from three aspects: “individual and family characteristics of farmers”, “cognition of farmers” and “external factors”. The survey was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
4
6
1
1
Order By: Relevance
“…Based on the field research data in Hainan Province, this paper empirically analyzes the factors influencing farmers’ green production behavior–willingness deviation, and explores the logical hierarchy among the influencing factors. The main findings are as follows: firstly, 94.72% of the farmers’ green production behavior and willingness are not consistent; there are deviations between the farmers’ green production behavior and willingness, which is consistent with the results obtained by Guo et al (2021) [ 9 ], Liu et al (2021) [ 17 ] and Xu et al (2021) [ 60 ], indicating that there is also a serious behavior–willingness deviation in the process of green agricultural production in tropical China. Secondly, age, number of dependents, peer influence, and social network have a significant positive effect on farmers’ green production behavior–willingness deviation, while ethnicity, education, land fragmentation, agricultural expenditure, land transfer, neighborhood learning, and green production cognition have a negative influence on the deviation.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Based on the field research data in Hainan Province, this paper empirically analyzes the factors influencing farmers’ green production behavior–willingness deviation, and explores the logical hierarchy among the influencing factors. The main findings are as follows: firstly, 94.72% of the farmers’ green production behavior and willingness are not consistent; there are deviations between the farmers’ green production behavior and willingness, which is consistent with the results obtained by Guo et al (2021) [ 9 ], Liu et al (2021) [ 17 ] and Xu et al (2021) [ 60 ], indicating that there is also a serious behavior–willingness deviation in the process of green agricultural production in tropical China. Secondly, age, number of dependents, peer influence, and social network have a significant positive effect on farmers’ green production behavior–willingness deviation, while ethnicity, education, land fragmentation, agricultural expenditure, land transfer, neighborhood learning, and green production cognition have a negative influence on the deviation.…”
Section: Discussionsupporting
confidence: 85%
“…Under the government’s publicity and incentives, environmental protection and sustainable development are nothing new in China. Most Chinese farmers are willing to adopt green production techniques [ 9 ]. However, although most farmers have accepted and agreed to the value of ecological production, their traditional production behavior has not changed significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al, studied the behavior and willingness of farmers to apply biopesticides. The results show that education, rice planting scale, cognition of biopesticides, social norms and other factors will affect farmers' adoption of biopesticides [33]. Sheikh et al, believe that when adopting no tillage technology, personal characteristics are the main influencing factors, including education level, identity of renters, attitude towards new technology risks and technology promotion of extension personnel [34].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, willingness predicts and leads to the realization of the corresponding actual behavior of an individual; however, many previous studies have confirmed that there is a deviation between willingness and behavior in real life, such as in commodity consumption , services purchases (Qu et al, 2022), e-commerce adoption (Li et al, 2020), and land transfer (Zhang et al, 2020a). This deviation has been further identified in the field of pro-environmental behaviors such as green consumption (Rausch and Kopplin, 2021;Wang et al, 2021;Ma et al, 2022;Qiu et al, 2022), green agriculture (Guo et al, 2021;Li et al, 2021), garbage classification (Kuang and Lin, 2021;Zhang et al, 2022;Zhou et al, 2022), bird conservation donation (Eylering et al, 2022), and renewable energy development support (Fang et al, 2021). All these studies concluded that the willingness of an individual is higher than the actual behavior demonstrates.…”
Section: Introductionmentioning
confidence: 99%